Efisiensi Syariah dalam Era Digital: Tinjauan Sistematis terhadap Pengelolaan Zakat di Era QRIS dan Fintech Islam - Siregar, Tetty Handayani; Majid, Shabri Abd; Sugianto (JSE: Jurnal Sharia Economica, 2025)
Digital transformation in zakat management is inevitable amidst the development of Islamic financial technology. This study aims to systematically examine the influence of digital technology on the efficiency of zakat management in Indonesia and other Muslim countries. Using the Systematic Literature Review (SLR) approach based on PRISMA 2020, this article analyzes 10 scientific literature published between 2015–2025. The results of the study show that the use of technology such as QRIS, SIMBA, digital wallets, and Islamic fintech can increase the operational efficiency of zakat institutions, especially in terms of service speed, transparency, and cost reduction. However, this effectiveness is not evenly distributed because there are still obstacles in the readiness of human resources, infrastructure, and institutional integration. The study also found that there is no standardized efficiency evaluation model among zakat managers. This study recommends the importance of cross-sector collaboration, strengthening the digital capacity of amil, and integrating digital systems between institutions to create a more efficient and sustainable digital zakat ecosystem. These findings are expected to be a reference in policy making and developing a digital zakat system that is adaptive to the challenges of the 5.0 era